Crystallization and architecture engineering of ZnWO4 for enhanced photoluminescence - Li, Meiting; Wang, Xuejiao; Zhu, Qi; Ji-Guang, Li; Byung-Nam, Kim (CrystEngComm, 2020)
Oxalic acid (H2C2O4) and (NH4)2SO4 were originally examined as crystallization and architecture directing reagents for the hydrothermal synthesis of ZnWO4, with the pivotal roles of the C2O42−/Zn2+ (R) and SO42−/Zn2+ (R′) molar ratios and hydrothermal temperature/duration investigated in detail. It was clearly demonstrated that C2O42− remarkably altered the reaction pathway and suppressed the intrinsic 1D growth of ZnWO4, eventually leading to 2D crystallites with exposed ab planes. (NH4)2SO4 further promoted 2D growth and self-assembly of the ZnWO4 crystallites, leading to flower-like architectures of up to ∼2.5 μm sized large microplates. Photoluminescence properties were thoroughly analyzed and discussed for the representative ZnWO4 and (Zn0.98Eu0.02)WO4 products after 700 °C calcination to show the importance of crystallite/architecture engineering.